(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article analyzes the philosophical risks of civil aviation safety. The main aim of the study is to examine the concept of safety from philosophical, ethical, and technical perspectives, highlighting the role of the human factor and moral responsibility. The study draws on the concepts of Heidegger, Ellul, Jonas, and other philosophers to explore the philosophical and ethical foundations of aviation safety. It examines the interconnection of technical, human, and moral components, as well as issues related to safety levels and acceptable risk.